Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing 2015 - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This edited book presents scientific results of the 16th IEEE/ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD 2015) which was held on June 1 - 3, 2015 in Takamatsu, Japan. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the numerous fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. Research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them.
On the Accelerated Convergence of Genetic Algorithm Using GPU Parallel Operations -- A GPU-Based Pencil Beam Algorithm for Dose Calculations in Proton Radiation Therapy -- Incremental Max-Margin Learning for Semi-Supervised Multi-Class Problem -- Improving Hypervisor based SSD Caching with Logically Partitioned Blocks and Scanning in Cloud Environment.- Emotional Scene Retrieval from Lifelog Videos Using Evolutionary Feature Creation -- On Solving the Container Problem in a Hypercube with Bit Constraint -- Algorithms for Removing Node Overlaps with Some Basic Nodes.-Significant Frequency Range of Brain Wave Signal for Authentication -- Simple Models Characterizing the Cell Dwell Time with a Log-Normal Distribution -- A Method of Ridge Detection in Triangular Dissections Generated by Homogeneous Rectangular Dissections -- Architecture for Wide Area Appliance Management -- Towards a Model Level Replication Technique for Fault Tolerant Systems Using AADL -- Model Inference of Mobile Applications with Dynamic State Abstractions -- Automatic Generation of S-LAM Descriptions from UML/MARTE for the DSE of Massively Parallel Embedded Systems -- Automatic Translation of OCL Meta-Level Constraints into Java Meta-programs.-Towards a Formal Model for Dynamic Networks Through Refinement and Evolving Graphs -- An Iterated Variable Neighborhood Decent Hyperheuristic for the Quadratic Multiple Knapsack Problem.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence